ANALISIS FAKTOR RISIKO YANG DAPAT DIKENDALIKAN PADA KEJADIAN PJK USIA PRODUKTIF - Desta Saesarwati; Prijono Satyabakti (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2016)
Coronary heart disease is one of cardiovascular disease dan being number one of mortalitycause in world. Coronay heart disease is begun with atherosclerosis. Atherosclerosis is process ofaccumulation of cholesterol in wall of heart’s blodd vessels that causes stenosis (obstruction). Thesedays coronary heart disease attacked productive people. Some risk factors of coronary heart diseaseare smoking habit, physical inactivity, hypertension, intake of unhealthy food, and stress. The aims ofthis research was to analyse modifi able risk factors of coronary heart disease in productive age thatconsists of smoking habit, physical inactivity, and stress. This study was an analytical study that usedcross sectional design conducted at cardiology clinic RSU Haji Surabaya at March-May 2016. Thepopulation in this study were all patients of cardiology clinic in RSU Haji Surabaya with 91 patientsas samples. The data described that there were no signifi cant correlation between smoking habit (p =0,22), physical inactivity (p = 0,79), dan stress (p = 0,06) with the incident of coronary heart diseasein productive age, and there was signifi cant correlation between passive smoker status with correlationof coronary heart disease in productive age (p = 0,01). The conclusion are there were no signifi cantcorrelation between smoking habit, physical inactivity, and stress with incident of coronary heart diseasein productive age, and there was signifi cant correlation between passive smoker status with incident ofcoronary heart disease in productive age.Keywords: risk factors, coronary heart disease, productive age